Die Förderung sozialen Engagements Drittstaatenangehöriger in Vereinen als Aufgabe der Sozialen Arbeit (Perspektiven - Soziale Arbeit in der Migrationsgesellschaft und muslimische Wohlfahrtspflege, 2024)
Third-country nationals are strongly underrepresented among volunteers, as noted by Johannes Eick and Markus Ottersbach in their contribution “Promoting the social engagement of third-country nationals in associations as a task of social work. Findings and recommendations from an evaluation study in North Rhine-Westphalia” in this issue. The authors identify the continued presence of local associations, the development of sustainable relationships and the long-term support of new volunteers as key factors for success.  3. Bauer